High-Throughput Sequencing Reveals the Regulatory Networks of Transcriptome and Small RNAs During the Defense Against Marssonina brunnea in Poplar - Liao, Yangwenke; Zhang, Qingyue; Cui, Rongrong; Xu, Xin; Zhu, Fuyuan; Cheng, Qiang; Li, Xiaogang (Frontiers in Plant Science, 2021)
MicroRNAs are implicated in the adjustment of gene expression in plant response to biotic stresses. However, the regulatory networks of transcriptome and miRNAs is still poorly understood. In the present study, we ascertained the induction of genes for miRNA biosynthesis in poplar defense to a hemibiotrophic fungus Marssonina brunnea, and afterwards investigated the molecular regulatory networks by performing comprehensive sequencing analysis of mRNAs and small RNAs in M. brunnea-inoculated leaves. Differentially expressed genes in M. brunnea-infected poplar are mainly involved in secondary metabolisms, phytohormone pathways, the recognition of pathogens and MAPK pathway in plant, with real-time quantitative PCR (qPCR) validating the mRNA-seq results. Furthermore, differentially expressed miRNAs including MIR167_1-6, MIR167_1-12, MIR171_2-3, MIR395-13, MIR396-3, MIR396-16, MIR398-8 and MIR477-6 were identified. Through psRobot and TargetFinder programs, MIR167-1-6, MIR395-13, MIR396-3, MIR396-16 and MIR398-8 were annotated to modulate the expression of genes implicated in transportation, signaling and biological responses of phytohormones and activation of antioxidases for plant immunity, respectively. Besides, novel miRNAs including Novel MIR8567, Novel MIR3228, Novel MIR5913 and Novel MIR6493 were identified using the Mireap online program according to the selected differentially expressed genes (DEGs) of interest, which function in the transcriptional regulation of lignin biosynthesis for poplar anti-fungal response. Our work underlines the roles of miRNAs in the regulation of transcriptome in anti-fungal response of poplar and provide a new idea for molecular breeding of woody plant.